Clinicopathologic findings in children who died following Klebsiella pneumoniae bloodstream infection. (September 2019) - Buys, Heloise; Muloiwa, Rudzani; Williams, Gavin L.; Eley, Brian; Pillay, Komala
Abstract: Background: Klebsiella pneumoniae bloodstream infection (KPBSI) is strongly linked to hospitalisation and can lead to significant morbidity and mortality. There is little data describing the autopsy findings of KPBSI in children. Methods: We conducted a retrospective review of clinicopathologic findings of children who died during the course of KPBSI at a children's hospital in Cape Town, South Africa. Results: Fifteen hospitalised children who died and had autopsies were included in this analysis. Their median age (interquartile range, IQR) was 4 (1–22) months, 2 (20%) were HIV-infected, and 10 (67%) were moderately or severely underweight. The median time to death from the time of positive blood culture was 1 (IQR 0–5) day. Notable autopsy findings were sepsis-induced multiorgan failure in many cases including thymic involution, oesophageal erosions, adrenal haemorrhage, acute tubular necrosis and lung parenchymal destruction. Other histologic findings included disseminated intravascular coagulopathy, necrotising inflammation in many organs; and in four of five children biofilm formation. Conclusion: KPBSI may cause widespread necrotic tissue. Highlights: Klebsiella pneumoniae bloodstream infections are a major clinical problem in hospitalised children There is a paucity of published research in the field of autopsy findings Our paper brings a different dimension to the understanding of Enterobacteriaceae infections in children Early detection of biofilm formation in tissue specimens may indicate sub-optimal responses to antibiotics More research is needed on understanding of the molecular mechanisms of Klebsiella pneumoniae -related biofilm formation